Functional inference of long non-coding RNAs through exploration of highly conserved regions - Liu, Zhongpeng; Guo, Tianbin; Yin, Zhuoda; Zeng, Yanluo; Liu, Haiwen; Yin, Hongyan (Frontiers in Genetics, 2023)
Long noncoding RNAs (lncRNAs), which are generally less functionally characterized or less annotated, evolve more rapidly than mRNAs and substantially possess fewer sequence conservation patterns than protein-coding genes across divergent species. People assume that the functional inference could be conducted on the evolutionarily conserved lncRNAs, as they are most likely to be functional. In the past decades, substantial progress has been made in discussions on the evolutionary conservation of noncoding genomic regions from multiple perspectives. However, understanding their conservation and the functions associated with sequence conservation in relation to further corresponding phenotypic variability or disorders still remains incomplete. Accordingly, we determined a highly conserved region (HCR) to verify the sequence conservation among lncRNAs and systematically profiled homologous lncRNAs clusters in human and mouse based on detections of HCR. Moreover, according to the homolog clustering, we explored the potential function inference via HCR on representative lncRNAs. On lncRNA XACT, we investigated the potential functional competence between XACT and lncRNA XIST by recruiting miRNA-29a, regulating the downstream target genes. In addition, on lncRNA LINC00461, we examined the interaction relationship between LINC00461 and SND1. This interaction or association may be perturbed during the progression of glioma. Besides, we have constructed a website with user-friendly web interfaces for searching, analyzing, and downloading to present the homologous clusters of human and mouse. Collectively, homolog clustering via HCR definition and detection on lncRNAs, as well as the functional explorations on representative sequences in our research, would provide new evidence for the potential function of lncRNAs. Our results on the remarkable roles of lncRNAs would presumably provide a new theoretical basis and candidate diagnostic indicators for tumors.